Neuroprotection by IL-6 Is Mediated by STAT3 and Antioxidative Signaling in Ischemic Stroke - Jung, Joo Eun (2011)
BACKGROUND AND PURPOSE: Interleukin-6 (IL-6) has been shown to have a neuroprotective effect in brain ischemic injury. However, its molecular mechanisms are still poorly understood. In this study, we investigated the neuroprotective role of the IL-6 receptor (IL-6R) by IL-6 in the reactive oxygen species defense system after transient focal cerebral ischemia (tFCI). METHODS: IL-6 was injected in mice before and after middle cerebral artery occlusion. Co-immunoprecipitation assays were performed for analysis of IL-6R association after tFCI. Primary mouse cerebral cortical neurons were transfected with small interfering RNA probes targeted to IL-6Rα or gp130 and were used for chromatin-immunoprecipitation assay, luciferase promoter assay, and cell viability assay. Reduction in infarct volumes by IL-6 was measured after tFCI. RESULTS: IL-6R was disrupted via a disassembly between IL-6Rα and gp130 associated by protein oxidation after reperfusion following tFCI. This suppressed phosphorylation of signal transducer and activator of transcription 3 (STAT3), and finally induced neuronal cell death via a decrease in manganese-superoxide dismutase (Mn-SOD). However, IL-6 injections prevented disruption of IL-6R against reperfusion after tFCI, consequently restoring activity of STAT3 through recovery of the binding of STAT3 to gp130. Moreover, IL-6 injections restored the transcriptional activity of the Mn-SOD promoter through recovery of the recruitment of STAT3 to the Mn-SOD promoter, and reduced infarct volume after tFCI. CONCLUSIONS: This study demonstrates that IL-6 has a neuroprotective effect against cerebral ischemic injury through IL-6R-mediated STAT3 activation and Mn-SOD expression.